The modern TV audience in Kazakhstan (Herald of Journalism, 2018)
In this article the author considers the impact of television on the modern TV viewer. The author defines factors that affect the change in the psychology of modern television audience and the major changes that occur in the psychology of the recipient.Also the author considers such problems as reduced concentration of attention, violation of clear thinking and change processes of remembering